2006
DOI: 10.1007/s11010-005-9110-6
|View full text |Cite
|
Sign up to set email alerts
|

Erdosteine Against Acetaminophen Induced Renal Toxicity

Abstract: Acetaminophen (APAP) induced toxicities have been a major problem in clinical practice. The aim of the present study was to demonstrate a possible protective role of erdosteine, a mucolytic agent having antioxidant properties via its active metabolites, on APAP induced renal damage in rats. Female Wistar Albino rats were divided into groups including control, erdosteine (150 mg/kg, oral), APAP (1 g/kg, oral) APAP+erdosteine (150 mg/kg, oral) and APAP+erdosteine (300 mg/kg, oral). APAP treatment caused lipid pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 25 publications
8
43
2
Order By: Relevance
“…In this study, we demonstrated that the administration of Science Publications AMJ overdose PCM (750 mg kg −1 ) for 28 consecutive days was able to induce nephrotoxicity in rats, as demonstrated by the significantly increased level of plasma urea and creatinine and significant decreases in serum total proteins. These results are in agreement with that observed by Isik et al (2006) who noticed an elevation in serum urea and creatinine in rats after 1 g kg −1 b.w. of PCM administration.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we demonstrated that the administration of Science Publications AMJ overdose PCM (750 mg kg −1 ) for 28 consecutive days was able to induce nephrotoxicity in rats, as demonstrated by the significantly increased level of plasma urea and creatinine and significant decreases in serum total proteins. These results are in agreement with that observed by Isik et al (2006) who noticed an elevation in serum urea and creatinine in rats after 1 g kg −1 b.w. of PCM administration.…”
Section: Discussionsupporting
confidence: 93%
“…Different studies have shown that APAP-induced renal damage is consistent with acute tubular necrosis. [1][2][3][22][23][24] Direct toxic effect of APAP on capillary wall may be responsible from APAP-induced acute tubular necrosis. The other histopathological findings of APAPinduced nephrotoxicity in rats are tubular epithelial degeneration, proximal tubular vacuolization, cell desquamation, necrosis and cellular debris in the proximal tubules, and cortical interstitial congestion.…”
Section: Discussionmentioning
confidence: 99%
“…Renal insufficiency occurs in approximately 1-2% of the patients with an overdose of APAP. [1][2][3][4] The main toxicity of APAP is the result of drug metabolism in the liver and other organs. At the pharmacologic doses, APAP is metabolized mostly to inactive compounds via Phase II reactions by conjunction by sulfate and glucuronide.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it is showed that acetaminophen increases reactive oxygen radicals such as nitric oxide and this also contributes to cell damage. 5,6 In our patient, nephrotoxicity without hepatotoxicity occurred after acetaminophen overdose. Some clinical situations such as alcohol ingestion, low protein diets, starvation, and inducing the P-450 enzymatic system with drugs (carbamazepine, phenobarbital, phenytoin, and so on) may enhance the nephrotoxicity of acetaminophen.…”
Section: Discussionmentioning
confidence: 57%